Rational designed microstructure pressure sensors with highly sensitive and wide detection range performance. (10th December 2022) - Ni, Yimeng; Liu, Lexin; Huang, Jianying; Li, Shuhui; Chen, Zhong; Zhang, Weiying; Lai, Yuekun
Highlights: High sensitivity (26.55 kPa −1 ) and wide work range (0.9 Pa-140 kPa) pressure sensor was demonstrated. Micro-nano hierarchical structure sponge surface with random uneven pattern. PDMS sponge fabricated via mixed sacrifice template and electrostatic self-assembly methods. The pressure sensor has great potential for healthcare and human-machine interfaces. Abstract: Highly sensitive pressure sensors are often deployed in human-machine interaction area, touch screen and human motion detection. However, there are still great challenges to fabricating with high sensitivity pressure sensor with wide-range detection. Herein, we developed a new strategy to fabricate a highly sensitive pressure sensor using sandpaper and improve its detection range using a sacrificial template. It was the fthatirst time to combine microstructure processing with the sacrificial template method to fabricate pressure sensor. The microstructure of sandpaper endowed the sensor with high sensitivity, and the elastic substrate enhanced the sensor ability to resist high pressure without being damaged. The fabricated sensor device exhibits a superior sensitivity of 39.077 kPa −1 in the range from 50 kPa to 110 kPa with a broad linear response. Remarkably, high pressure ceiling (<160 kPa) ensures that the sponge could be applied in different practical conditions to monitor a range of subtle human motions including finger, wrist bending, and pulse. For applications, the sensor device can not only detect the foot stepping behavior (0.7 MPa) but also produce an obvious response to an extremely slight paper (9 mg, ∼0.9 Pa). The successful preparation of this micro-structured elastic sponge material provided new ideas for exploring its potential applications in pressure sensors and flexible wearable electronic devices.